Implementasi BIM 5D pada Pekerjaan Beton Bertulang pada Proyek Pembangunan Gedung Tower SSC di Balikpapan - Arman Sulfian Dani; Reno Pratiwi; Suheriah Mulia Devi (Jurnal Talenta Sipil, 2026)
The calculation of construction cost estimates by planning consultants generally still relies on Microsoft Excel. This conventional method is prone to errors due to inaccuracies in data interpretation and the complexity of building design calculations. Such conditions may result in significant discrepancies, potentially leading to cost overruns. Therefore, a more efficient and accurate approach to cost estimation is required, one that can also present project information comprehensively. This study aims to compare the calculation results of volume and Cost Budget Plan (RAB) for reinforced concrete works between the conventional method used by planning consultants and the Building Information Modeling (BIM) 5D method. The research was conducted as a case study on the SSC Tower Building Project in Balikpapan using Autodesk Revit software to generate BIM-based cost estimates. The results indicate that the difference in volume calculation for reinforcement and concrete works is 0%, and the difference in cost estimation for reinforced concrete works is also 0%. This finding suggests that the BIM 5D method produces results consistent with those of the conventional consultant method. In conclusion, BIM 5D application in cost estimation provides results as accurate as the conventional method, with added advantages in visualization, interactive project information, and efficiency in the decision-making process.